Risiko Postur Janggal dengan Kejadian Gangguan Otot Rangka Akibat Kerja (Gotrak) pada Terapis Pijat: Risiko Postur Janggal dengan Kejadian Gangguan Otot Rangka Akibat Kerja (Gotrak) pada Terapis Pijat - Dodi, Muhammad; Tresnaningsih, Erna; Mitra, Mitra; Zaman, M. Kamali; Putri, Retno (Jurnal Kesehatan Komunitas, 2018)
Many massage therapists experience work-related skeletal muscle disorders (WMSDs). This study aimed to determine the proportion of the incidence of WMSDs and the relationship with the incident of posture WMSDs in massage therapists. The type of research was quantitative analytic observational with cross sectional design. The type of massage under study was traditional massage. Population and sample were massage therapist in Pekanbaru City 2017 with sample size 77 people taken by consecutive sampling technique. Data collection and processing used interviews with quesonnaires, documentation and Rapid Upper Limb Assesment (RULA). Level of risk of WMSDs incident used semi-qualitave analysis and nordic body map. WMSDs incidence rate in massage therapist was high enough that was 61%. The results showed that the variables significantly correlated with incidence of WMSDs were odd posture (POR: 8,30, 95% CI: 2,401-8,753), length of work (POR: 10,109; 95% CI:2,567-39,811) and age (POR: 7,649 95% CI: 2,567-39,811). The most WMSDs complaints on both hands were 57 people (74%), left shoulder and right shoulder were 27 people (35.1%) and lower back were 19 (24,7%). It is advisable in massage therapists to avoid awkward posture while massaging clients by improving work posture, posion while massaging and placing the equipment used within the reach of the hand.